Examining Impacts of Acidic Bath Temperature on Nano-Synthesized Lead Selenide Thin Films for the Application of Solar Cells. (11th January 2022) - Abel, Saka; Tesfaye, Jule Leta; Nagaprasad, N.; Shanmugam, R.; Dwarampudi, L. Priyanka; Deepak, Tyagi; Zhang, Hongxia; Krishnaraj, Ramaswamy; Stalin, B.
Abstract : The influence of bath temperature on nano-manufactured PbSe (lead selenide) films was successfully generated by utilizing CBD on the acid solution's metal surface tool. Pb (NO3 )2 was employed as a lead ion source as a precursor, while Na2 O4 Se was used as a selenide ion source. The XRD characterization revealed that the prepared samples are the property of crystalline structure (111), (101), (100), and (110) Miller indices. The scanning electron microscope indicated that the particles have a rock-like shape. There was a decrement of energy bandgap that is from 2.4 eV to 1.2 eV with increasing temperature 20°C–85°C. Thin films prepared at 85°C revealed the best polycrystal structure as well as homogeneously dispersed on the substrate at superior particle scales. The photoluminescence spectrophotometer witnessed that as the temperature of the solution bath increases from 20°C to 85°C, the average strength of PL emission of the film decreases. The maximum photoluminescence strength predominantly exists at high temperatures because of self-trapped exciton recombination, formed from O2 vacancy and particle size what we call defect centres, for the deposited thin films at 45°C and 85°C. Therefore, the finest solution temperature is 85°C.